IDENTIFICATION OF BEACH DEVELOPMENT ON THE NEAR MANADO PORT AND TONDANO RIVER - Bawangun, Yongky W.; Djamaluddin, Rignolda; Manengkey, Hermanto W. K. (Sam Ratulangi University, 2013)
Coastal areas have been subjected to tourism activities, settlement and variousforms of industries. To support any development projects, coastal environment werereclaimed to be land, seaport and coastal protective constructions. Physically, coastconsists of several landscapes and one of them is in form of ‘beach’. In order to usecoastal environment properly and sustainably, there is a need for user to understand anyprocesses that work on the coast. Erosion is of importance problem in the coast, and thiscan be the reason for settlements and facilities destruction. The existence of jetty andnew land around the Manado Port has changed the hidrodynamic condition nearby. Thischange has facilitated the change in the sediment distribution near the mouth of TondanoRiver at certain level.